Synthesis of N-Arylisatins Using Different Heterogeneous Catalyst Under Microwave Irradiations - Singh, Ravinder; Kumar, Ramesh (Asian Journal of Chemistry, 2013)
N-Arylisatins having both biological and medical properties are synthesized by the reaction of methyl-2-oxo-2-(arylamino)acetates and arynes using NaHCO3 in presence of different heterogeneous catalyst under microwave irradiations in high yield in shorter reaction time.